ANALISIS DEBT TO EQUITY RATIO (DER) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP HARGA SAHAM PADA PT. ASTRA GRAPHIA TBK. AMAR MAKRUF, M.RIMAWAN, M.Si, Ak.Ca., IMAM DARMAWAN, MM.Inov. - AMAR MAKRUF; M.RIMAWAN, M.Si, Ak.Ca; IMAM DARMAWAN, MM.Inov. (Universitas Mahendradatta, 2025)
This research aims to determine the analysis of Debt To Equity Ratio(DER) and Total Asset Turnover (TATO) on share prices at Pt. Astra Graphia Tbk. Theinstrument for this research is to use financial reports between the balance sheet and profitand loss reports at Pt. Astra Graphia Tbk, the data used in the research instrument is data ontotal debt, equity, sales, total assets and share prices from 2013 - 2022. Meanwhile, thesampling technique used is purposive sampling, the criteria are based on the availability ofup-to-date data and data research variables that will be used. The data in this research wasprocessed using SPSS. The hypothesis testing method uses a significance level of 5%. Theresearch results show that the Debt To Equity Ratio (DER) has no effect on stock prices,Total Asset Turnover (TATO) has no effect on stock prices, and the Debt To Equity Ratio(DER) and Total Asset Turnover (TATO) have no effect on stock prices.